Sisi Lain dari Putusan Mahkamah Agung RI Nomor 16/K/Ag/2010 Tentang Implementasi Wasiat Wajibah Terhadap Kewarisan Beda Agama; Kajian Dari Aspek Status Perkawinan Dan Wasiat Wajibah - Ahmatnijar, Ahmatnijar (IAIN Padangsidimpuan, 2019)
The judiciary is the most important element in human life because it is a place that demands those who lose their rights and can neutralize conflicting interests. The Religious Courts (PA) are part of this institution. The absolute competence of PA institutions includes handling inheritance matters. In Indonesia, there was an option for those who were Muslims to seek justice in the settlement of inheritance between the PA and the District Court (PN). The issuance of Marriage Law (UUP) number 1 of 1974 with the principle of Islamic personality is the answer to this option. However, the settlement of the case of inheritance of different religions has not been explicitly regulated in this regulation, so it still leaves new issues such as the case of the inheritance of the late Muhammad Armaya bin Renreng alias Armaya Renreng, Islam, with his wife Evie Lany Mosinta, Christian.